Immune Profile of Obese People and In Vitro Effects of Red Grape Polyphenols on Peripheral Blood Mononuclear Cells. (24th January 2017) - Magrone, Thea; Jirillo, Emilio; Spagnoletta, Anna; Magrone, Manrico; Russo, Matteo Antonio; Fontana, Sergio; Laforgia, Flavia; Donvito, Ilaria; Campanella, Angelo; Silvestris, Franco; De Pergola, Giovanni
Abstract : The in vitro ability of polyphenols, extracted from red grape, to modulate peripheral blood mononuclear cell responses has been evaluated in 20 obese (Ob) people. With regard to cytokine release in response to phorbol myristate acetate (PMA), levels of interleukin-2 (IL-2), interferon- γ (IFN- γ ), IL-4, IL-10, and IL-17 were higher in the Ob than in healthy (H) subjects. Vice versa, IL-21 concentrations were detected only in H people but they were undetectable in the Ob counterpart. In general terms, levels of IL-1 β, IL-6, IL-8, and tumor necrosis factor- α were higher in Ob people when compared to H controls. On the other hand, polyphenols did not modify IFN- γ, IL-4, and IL-17 levels. However, an increase in IL-2 was observed in H individuals, whereas its levels were decreased in the Ob counterpart. Polyphenols significantly increased IL-10 release from H donors, whereas a trend to increase was observed in Ob people. In addition, polyphenols were able to significantly increase levels of H IL-21, while this was not the case in Ob people. Since IL-21 is an inducer of Th17 cells, it is likely that polyphenols may suppress the sources of this cytokine via production of IL-10. Accordingly, polyphenols decreased IL-1 β and IL-6 release in comparison to H controls.